Geology and Mineral Resources of Phalamdada-Dhuwakot Section of West-Central Nepal, Lesser Himalaya - Bhattarai, Arjun; Paudyal, Kabiraj (Bulletin of the Department of Geology, 2018)
Geological mapping was carried out along the Phalamdanda-Dhuwakot section of west-central Nepal in the Lesser Himalaya. The aim of geological mapping was to prospect the metallic mineral resources in the area especially to assess the geological control of mineralization as prognostic mapping and study the genesis of mineralization. The area has developed low-grade metamorphic rocks of the Nawakot Group. Geological rock units like the Kuncha Formation, Fagfog Quartzite, Dandagaon Phyllite, Nourpul Formation and Dhading Dolomite are mapped in the area. Jal Bhanjyang Thrust carries the more older rocks of the Nourpul Formation over the Dhading Dolomite. The area is highly deformed as indicated by presence of folds. Outliers of Fagfog Quartzite and Dhading Dolomite are developed at the core part of the syncline. Phalamdada iron and Anbu Khaireni as well as Dharapani copper are the major metallic deposits reported in the area. Both deposits are considered as the syngenetic in nature. Bulletin of Department of Geology, vol. 20-21, 2018, pp:59-64